2021
DOI: 10.1007/s12639-021-01376-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular description of a new species of Myxobolus (Myxosporea: Myxobolidae) infecting Planiliza macrolepis (Smith, 1846) from India

Abstract: The present paper describes a novel species of Myxobolus parasitizing the gill laments of the largescale mullet, Planiliza macrolepis from Cochin backwaters, Kerala, India. The parasite develops in the gill laments; plasmodia elongated, milky white, measured 1.37 -2.18 (1.78 ± 0.35) mm x 0.07-0.12 (0.10 ± 0.02) mm in size. Mature myxospores ovoid in valvular view, biconvex in sutural view with smooth shell valves and measured 6.24 -7.02 (6.63 ± 0.23) × 5.01 -6.18 (5.68 ± 0.25) μm in size. Polar capsules equal,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Histopathology revealed that the gill filament of the infected S. paramamosain appeared slightly swollen, accompanied by a detached cuticle. These alterations in the gill surface architecture can reduce the gaseous exchange capacity of the gills [24]. It has been reported that some ciliates such as Synophrya sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathology revealed that the gill filament of the infected S. paramamosain appeared slightly swollen, accompanied by a detached cuticle. These alterations in the gill surface architecture can reduce the gaseous exchange capacity of the gills [24]. It has been reported that some ciliates such as Synophrya sp.…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium contained sterilized sea water (salinity = 25 psu), 10% (v/v) heat-inactivated fetal bovine serum (FBS, Gibco, Billings, MT, USA) and 5% crab soup (100 g crab muscle and 1000 mL water, boiled to 100 mL). The temperature was maintained at 12-14 • C. In order to observe its growth curve, the number of ciliates contained in 10 µL of the culture medium was counted three times at 0, 6,12,18,24,30,36,42,48,54,60,66,72,78, 84 and 90 h using light microscopy (Nikon Eclipse Ni-U) as described by Parama [19].…”
Section: Mesanophrys Sp Cultivationmentioning
confidence: 99%